Physical, mechanical, and morphological performances of arrowroot (Maranta arundinacea) fiber reinforced arrowroot starch biopolymer composites - Tarique, J.; Zainudin, E.; Sapuan, S.; Ilyas, R.; Khalina, A. (MDPI, 2022)
This research is driven by stringent environmental legislation requiring the consumption and use of environmentally friendly materials. In this context, this paper is concerned with the development and characterization of thermoplastic arrowroot starch (TPAS) based biocomposite films by incorporating arrowroot fiber (AF) (0–10%) into a glycerol plasticized matrix by using the solution casting method. Developed TPAS/AF composite films were investigated, such as physical, morphological (FESEM), tensile, and tear strength characteristics. The tensile and tear strengths of TPAS/AF composites were increased significantly from 4.77 to 15.22 MPa and 0.87 to 1.28 MPa, respectively, as compared to the control TPAS films, which were 2.42 MPa and 0.83 MPa, respectively, while elongation was significantly decreased from 25.57 to 6.21% compared to control TPAS film, which was 46.62%. The findings revealed that after the fiber was reinforced, the mechanical properties were enhanced, and the optimum filler content was 10%. Regardless of fiber loadings, the results of water absorption testing revealed that the composite films immersed in seawater and rainwater absorbed more water than distilled water. Overall, the results of this research focus on providing information on biopolymer composite film and revealing the great potential it has for the food packaging industry.